Chapter 1
Lookup tables for all problems in current book

1.1 section 1
1.2 section 2

1.1 section 1

Table 1.1: Lookup table

ID

problem

ODE

9072

1

\(y^{\prime \prime } = 0\)

9073

2

\({y^{\prime \prime }}^{2} = 0\)

9074

3

\({y^{\prime \prime }}^{n} = 0\)

9075

4

\(a y^{\prime \prime } = 0\)

9076

5

\(a {y^{\prime \prime }}^{2} = 0\)

9077

6

\(a {y^{\prime \prime }}^{n} = 0\)

9078

7

\(y^{\prime \prime } = 1\)

9079

8

\({y^{\prime \prime }}^{2} = 1\)

9080

9

\(y^{\prime \prime } = x\)

9081

10

\({y^{\prime \prime }}^{2} = x\)

9082

11

\({y^{\prime \prime }}^{3} = 0\)

9083

12

\(y^{\prime \prime }+y^{\prime } = 0\)

9084

13

\({y^{\prime \prime }}^{2}+y^{\prime } = 0\)

9085

14

\(y^{\prime \prime }+{y^{\prime }}^{2} = 0\)

9086

15

\(y^{\prime \prime }+y^{\prime } = 1\)

9087

16

\({y^{\prime \prime }}^{2}+y^{\prime } = 1\)

9088

17

\(y^{\prime \prime }+{y^{\prime }}^{2} = 1\)

9089

18

\(y^{\prime \prime }+y^{\prime } = x\)

9090

19

\({y^{\prime \prime }}^{2}+y^{\prime } = x\)

9091

20

\(y^{\prime \prime }+{y^{\prime }}^{2} = x\)

9092

21

\(y^{\prime \prime }+y^{\prime }+y = 0\)

9093

22

\({y^{\prime \prime }}^{2}+y^{\prime }+y = 0\)

9094

23

\(y^{\prime \prime }+{y^{\prime }}^{2}+y = 0\)

9095

24

\(y^{\prime \prime }+y^{\prime }+y = 1\)

9096

25

\(y^{\prime \prime }+y^{\prime }+y = x\)

9097

26

\(y^{\prime \prime }+y^{\prime }+y = x +1\)

9098

27

\(y^{\prime \prime }+y^{\prime }+y = x^{2}+x +1\)

9099

28

\(y^{\prime \prime }+y^{\prime }+y = x^{3}+x^{2}+x +1\)

9100

29

\(y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right )\)

9101

30

\(y^{\prime \prime }+y^{\prime }+y = \cos \left (x \right )\)

9102

31

\(y^{\prime \prime }+y^{\prime } = 1\)

9103

32

\(y^{\prime \prime }+y^{\prime } = x\)

9104

33

\(y^{\prime \prime }+y^{\prime } = x +1\)

9105

34

\(y^{\prime \prime }+y^{\prime } = x^{2}+x +1\)

9106

35

\(y^{\prime \prime }+y^{\prime } = x^{3}+x^{2}+x +1\)

9107

36

\(y^{\prime \prime }+y^{\prime } = \sin \left (x \right )\)

9108

37

\(y^{\prime \prime }+y^{\prime } = \cos \left (x \right )\)

9109

38

\(y^{\prime \prime }+y = 1\)

9110

39

\(y^{\prime \prime }+y = x\)

9111

40

\(y^{\prime \prime }+y = x +1\)

9112

41

\(y^{\prime \prime }+y = x^{2}+x +1\)

9113

42

\(y^{\prime \prime }+y = x^{3}+x^{2}+x +1\)

9114

43

\(y^{\prime \prime }+y = \sin \left (x \right )\)

9115

44

\(y^{\prime \prime }+y = \cos \left (x \right )\)

9116

45

\(y {y^{\prime \prime }}^{2}+y^{\prime } = 0\)

9117

46

\(y {y^{\prime \prime }}^{2}+{y^{\prime }}^{3} = 0\)

9118

47

\(y^{2} {y^{\prime \prime }}^{2}+y^{\prime } = 0\)

9119

48

\(y {y^{\prime \prime }}^{4}+{y^{\prime }}^{2} = 0\)

9120

49

\(y^{3} {y^{\prime \prime }}^{2}+y^{\prime } y = 0\)

9121

50

\(y y^{\prime \prime }+{y^{\prime }}^{3} = 0\)

9122

51

\(y {y^{\prime \prime }}^{3}+y^{3} y^{\prime } = 0\)

9123

52

\(y {y^{\prime \prime }}^{3}+y^{3} {y^{\prime }}^{5} = 0\)

1.2 section 2

Table 1.3: Lookup table

ID

problem

ODE

9124

1

\(y^{\prime \prime }+x y^{\prime }+y {y^{\prime }}^{2} = 0\)

9125

2

\(y^{\prime \prime }+\sin \left (x \right ) y^{\prime }+y {y^{\prime }}^{2} = 0\)

9126

3

\(y^{\prime \prime }+\left (1-x \right ) y^{\prime }+y^{2} {y^{\prime }}^{2} = 0\)

9127

4

\(y^{\prime \prime }+\left (\sin \left (x \right )+2 x \right ) y^{\prime }+\cos \left (y\right ) y {y^{\prime }}^{2} = 0\)

9128

5

\(y^{\prime \prime } y^{\prime }+y^{2} = 0\)

9129

6

\(y^{\prime \prime } y^{\prime }+y^{n} = 0\)

9130

8

\(y^{\prime } = \left (x +y\right )^{4}\)

9131

9

\(y^{\prime \prime }+\left (x +3\right ) y^{\prime }+\left (y^{2}+3\right ) {y^{\prime }}^{2} = 0\)

9132

10

\(y^{\prime \prime }+x y^{\prime }+y {y^{\prime }}^{2} = 0\)

9133

11

\(y^{\prime \prime }+\sin \left (x \right ) y^{\prime }+{y^{\prime }}^{2} = 0\)

9134

12

\(3 y^{\prime \prime }+\cos \left (x \right ) y^{\prime }+\sin \left (y\right ) {y^{\prime }}^{2} = 0\)

9135

13

\(10 y^{\prime \prime }+x^{2} y^{\prime }+\frac {3 {y^{\prime }}^{2}}{y} = 0\)

9136

14

\(10 y^{\prime \prime }+\left ({\mathrm e}^{x}+3 x \right ) y^{\prime }+\frac {3 \,{\mathrm e}^{y} {y^{\prime }}^{2}}{\sin \left (y\right )} = 0\)

9137

15

\(y^{\prime \prime }-\frac {2 y}{x^{2}} = x \,{\mathrm e}^{-\sqrt {x}}\)

9138

16

\(y^{\prime \prime }-\frac {y^{\prime }}{\sqrt {x}}+\frac {\left (x +\sqrt {x}-8\right ) y}{4 x^{2}} = x\)

9139

17

\(y^{\prime \prime }+\frac {2 y^{\prime }}{x}+\frac {a^{2} y}{x^{4}} = 0\)

9140

18

\(\left (-x^{2}+1\right ) y^{\prime \prime }-x y^{\prime }-c^{2} y = 0\)

9141

19

\(x^{6} y^{\prime \prime }+3 x^{5} y^{\prime }+a^{2} y = \frac {1}{x^{2}}\)

9142

20

\(x^{2} y^{\prime \prime }-3 x y^{\prime }+3 y = 2 x^{3}-x^{2}\)

9143

21

\(y^{\prime \prime }+\cot \left (x \right ) y^{\prime }+4 y \csc \left (x \right )^{2} = 0\)

9144

22

\(\left (x^{2}+1\right ) y^{\prime \prime }+\left (x +1\right ) y^{\prime }+y = 4 \cos \left (\ln \left (x +1\right )\right )\)

9145

23

\(y^{\prime \prime }+\tan \left (x \right ) y^{\prime }+\cos \left (x \right )^{2} y = 0\)

9146

24

\(x y^{\prime \prime }-y^{\prime }+4 x^{3} y = 8 x^{3} \sin \left (x \right )^{2}\)

9147

25

\(x y^{\prime \prime }-y^{\prime }+4 x^{3} y = x^{5}\)

9148

25

\(\cos \left (x \right ) y^{\prime \prime }+\sin \left (x \right ) y^{\prime }-2 y \cos \left (x \right )^{3} = 2 \cos \left (x \right )^{5}\)

9149

26

\(y^{\prime \prime }+\left (1-\frac {1}{x}\right ) y^{\prime }+4 x^{2} y \,{\mathrm e}^{-2 x} = 4 \left (x^{3}+x^{2}\right ) {\mathrm e}^{-3 x}\)

9150

27

\(y^{\prime \prime }-x^{2} y^{\prime }+x y = x^{m +1}\)

9151

28

\(y^{\prime \prime }-\frac {y^{\prime }}{\sqrt {x}}+\frac {\left (x +\sqrt {x}-8\right ) y}{4 x^{2}} = 0\)

9152

29

\(\cos \left (x \right )^{2} y^{\prime \prime }-2 \cos \left (x \right ) \sin \left (x \right ) y^{\prime }+\cos \left (x \right )^{2} y = 0\)

9153

30

\(y^{\prime \prime }-4 x y^{\prime }+\left (4 x^{2}-1\right ) y = -3 \,{\mathrm e}^{x^{2}} \sin \left (x \right )\)

9154

31

\(y^{\prime \prime }-2 b x y^{\prime }+b^{2} x^{2} y = x\)

9155

32

\(y^{\prime \prime }-4 x y^{\prime }+\left (4 x^{2}-3\right ) y = {\mathrm e}^{x^{2}}\)

9156

33

\(y^{\prime \prime }-2 \tan \left (x \right ) y^{\prime }+5 y = {\mathrm e}^{x^{2}} \sec \left (x \right )\)

9157

34

\(x^{2} y^{\prime \prime }-2 x y^{\prime }+2 \left (x^{2}+1\right ) y = 0\)

9158

35

\(4 x^{2} y^{\prime \prime }+4 x^{5} y^{\prime }+\left (x^{8}+6 x^{4}+4\right ) y = 0\)

9159

36

\(x^{2} y^{\prime \prime }+\left (-y+x y^{\prime }\right )^{2} = 0\)

9160

37

\(x y^{\prime \prime }+2 y^{\prime }-x y = 0\)

9161

38

\(x y^{\prime \prime }+2 y^{\prime }+x y = 0\)

9162

39

\(y^{\prime }+y \cot \left (x \right ) = 2 \cos \left (x \right )\)

9163

40

\(2 x y^{2}-y+\left (y^{2}+x +y\right ) y^{\prime } = 0\)

9164

41

\(y^{\prime } = x -y^{2}\)

9165

42

\(y^{\prime \prime \prime \prime }-y^{\prime \prime \prime }-3 y^{\prime \prime }+5 y^{\prime }-2 y = x \,{\mathrm e}^{x}+3 \,{\mathrm e}^{-2 x}\)

9166

43

\(x^{2} y^{\prime \prime }-x \left (6+x \right ) y^{\prime }+10 y = 0\)

9167

44

\(x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-5\right ) y = 0\)

9168

45

\(x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-5\right ) y = 0\)

9169

46

\(x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 0\)

9170

47

\(y^{\prime \prime \prime }-x y = 0\)

9171

48

\(y^{\prime } = y^{{1}/{3}}\)

9172

49

\([x^{\prime }\left (t \right ) = 3 x \left (t \right )+y \left (t \right ), y^{\prime }\left (t \right ) = -x \left (t \right )+y \left (t \right )]\)